Peningkatan Hasil Belajar Siswa Materi Organ Pencernaan Dengan Media Torso Organ Kelas V SD Negeri 3 Bakam Tahun Pelajaran 2023/2024 - Libur; M Iqbal Arrosyad; Gatot Afrianto (Universitas Muhammadiyah Bangka Belitung, 2025)
This study aims to improve students' learning outcomes on the topic of the human digestive system in fifth-grade students at SD Negeri 3 Bakam by using an organ torso as a teaching medium. The background of this research is the low learning outcomes and student participation in the learning process, which is attributed to the limited use of learning media. This classroom action research was conducted in two cycles, with the science teacher as the acting subject and fifth-grade students as recipients of the action in the first semester of the 2024 academic year. Data collected included students' learning outcomes and observations of their activity during the learning process. The results showed an increase in students' average learning outcomes by 25% from the pre-cycle to the second cycle. The percentage of learning completeness also increased, reaching 85% in the second cycle, while student activity levels during the learning process improved to 80%. Based on these findings, the use of demonstration methods with the aid of pictures and digestive organ cards effectively enhances both the activity and learning outcomes of fifth-grade students at SD Negeri 3 Bakam on science material related to the human digestive system.